PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN RELAWAN PEMADAM KEBAKARAN DI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA BENGKULU - Sari, Sentia Lopita; Heru Purnawan; Edi Darmawi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Fire is one of the disasters that frequently occurs in Indonesia and can cause major losses. Community involvement in forming volunteer fire fighters (Damkar) can help increase the effectiveness of fighting fires. The aim of this research is to analyze the relationship between community participation and the formation of firefighting volunteers in Bengkulu City. This research uses quantitative methods with Spearman correlation analysis techniques and determination. Data was collected through a survey of 31 respondents consisting of the community and firefighters volunteers in Bengkulu City. The results of the analysis show that there is a very strong and significant relationship between community participation and the formation of volunteer firefighters (Spearman correlation coefficient = 0.776, Sig. 2-tailed < 0.001). An R-Square value of 0.360 shows that 36% of the variability in the formation of Fire Volunteer can be explained by community participation. Community participation is an important factor in the formation of Fire Fighters volunteers in Bengkulu City. Apart from that, there are other factors that affect the formation of volunteer firefighters, such as support from the government, adequate infrastructure and cooperation with community organizations. The suggestions are as follows: It is necessary to make efforts to increase community participation in the formation of Fire Fighter volunteers, such as socialization and education, as well as the provision of adequate training and coaching.